Odpowiedzi

2010-01-03T17:20:27+01:00
1. a²b -( 3a × 3ba + 2b²a) + 15a²b²÷ 3x=
=a²b-(9a²b+2b²a)+5a²b²:x=a²b-9a²b-2b²a+5a²b²:x=-8a²b-2b²a+5a²b²:x
2. 12m²n⁵÷4mn⁵ + 21mn÷6m⁴n² × 2m⁵n - ½m=
=3m+7m⁴-1/2m=2,5m+7m⁴
3. [3u³v-3vu×5u² +(3u²v x-razy 2u - vu³)]÷ 4uv=
=(3u³v-15vu³+5vu³):4uv=-9u³v:4uv=-1 3/4u²
2010-01-03T17:25:12+01:00
1.
a²b -( 3a × 3ba + 2b²a) + 15a²b²÷ 3x=
a2b- (9a2b+2b2a) + 15a²b²÷ 3x=
a2b- 9a2b- 2b2a+ 15a²b²÷ 3x=
-8a2b-2b2a+ 15a²b²÷ 3x

3.
[3u³v-3vu×5u² +(3u²v x-razy 2u - vu³)]÷ 4uv=
( 3u³v- 15vu3+ (6u3v - vu3))/ 4uv=
3u³v- 15vu3+6u3v - vu3/ 4uv=
(9u3v- 14 vu3+6u3v)/4uv